A Study of Problem-Based Flipped Learning of Indonesian Vocational High School Students - Mustaqim, Burhan; Akhyar, Muhammad; Joyoatmojo, Soetarno (Journal of Teaching and Learning, 2025)
The integration of innovative learning models is essential for preparing vocational high school (VHS) students with 21st-century skills. This study aimed to explore the need for a Problem-Based Flipped Learning (PBFL) model with a Science Technology Engineering Mathematics (STEM) approach tailored to the needs of vocational high school students. Employing a qualitative descriptive method, the study involved 33 vocational high-school students and three mathematics teachers. Data was collected through interviews, observations, and questionnaires, with validity using triangulation. The results indicated that 87.9% of students endorsed the incorporation of PBFL-STEM, highlighting its efficacy in promoting collaboration and critical thinking. Educators emphasized its capacity to bridge theory and practice for enhanced industry alignment. Nonetheless, insufficient technology infrastructure and inadequate teacher preparation have been recognized as impediments to effective adoption. To tackle these issues, this study employed adaptive solutions, including the utilization of readily available technology (e.g., smartphones) and the provision of continuous teacher mentorship for better implementation. This research identified that the PBFL-STEM approach is extremely pertinent for vocational high schools, providing significant possibilities to cultivate students' 21st-century talents. This study showed that vocational schools can quickly fix these problems by encouraging teachers to improve their skills and ensuring that they understand the importance of new ways of learning for giving students a good education.